Surface roughness and wear properties of Al–Al2O3 metal matrix composites fabricated using friction stir processing - Fatchurrohman, Nanang; Azriee, Abdullah (Springer Singapore, 2018)
Friction stir processing (FSP) involves the mixing reinforcement particles on metal surface and the control of its dispersion is more difficult to attain with conventional techniques such as casting. The objective of present work was to perform tribology characterization of Al alloys Al-6061 and Al-6061 with 5 weight % Al2O3 produced using FSP. The parameters involved were rotation speed 1000, 1200 and 1400 rpm and traversed speed constant at 25 mm/min. The results show that the surface roughness with the presence of the reinforcement demonstrated better surface roughness compared to specimens with no reinforcement. Furthermore, high increment of the tool rotation speed indicates the declined value of the coefficient of friction of the specimen material.